(untitled) (Journal of Engineering, 2012)
In this study, the effect of ceramic coating on the performance and gases emission on diesel engine was investigated. A four-stroke, direct injected, single cylinder, diesel engine was tested at constant speed and at different load conditions without coating. Then, the inlet and exhaust valves faces were coated by about 500µm with ceramic materials. Ceramic layers were made of YttriaStabilized Zirconia (YSZ), and NiCrAl as a bond coat. The coating technique adapted in this work is the flame spray method. The engine with valves ceramiccoated research was tested for the same operation conditions of the engine (without coating). The results indicate a reduction in both fuel consumption by about 7.6% and particulate emissions by about (13% for HC and 14.5% for CO) with increasing in exhaust gases temperature after coating.